5(d-6)+6=

Simple and best practice solution for 5(d-6)+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(d-6)+6= equation:


Simplifying
5(d + -6) + 6 = 0

Reorder the terms:
5(-6 + d) + 6 = 0
(-6 * 5 + d * 5) + 6 = 0
(-30 + 5d) + 6 = 0

Reorder the terms:
-30 + 6 + 5d = 0

Combine like terms: -30 + 6 = -24
-24 + 5d = 0

Solving
-24 + 5d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 5d = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 5d = 0 + 24
5d = 0 + 24

Combine like terms: 0 + 24 = 24
5d = 24

Divide each side by '5'.
d = 4.8

Simplifying
d = 4.8

See similar equations:

| 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 | | x-9.51=2.4 | | -2b+8=-8 | | 241=5(5-7x)+8x | | 3c+5=-13 | | -5+(8-14)-(-4-9)= | | 17=3(p-4)+8 | | 10n-15=85 | | -2b+(-3)=7 | | -5.6+-15= | | 4m-13=15 | | 4.5x+13.5x=2.5-x+3 | | 3b+6(-6)=-12 | | -5(8-14)-(-4-9)= | | 4x-3x=2x+5 | | -2b+1=5 | | 2(3x-4)=-(4x+6) | | 3a+(-2)=-5 | | -27+17+(-1)= | | 2a+3c= | | 2x+(-4)=14 | | 4.5x+13.5=2.5-x+3 |

Equations solver categories